Analysis of Indonesia MSME's Perceptions of Interest in Adopting Sharia Financial Technology - Julaeha; Zulpahmi; Ummu Salma Al-Azizah; Sumardi (www.amertainstitute.com, 2025)
This study aims to identify the factors that affect interest of Micro, Small, and Medium Enterprises (MSMEs) to adopt sharia based financial technology (fintech) as an alternative to capital funding and to support business activities that are important in the sustainability of MSME. The study targets MSMEs in Indonesia, where sharia fintech represents an integration of contemporary financial technology and Islamic law principles. The research adopts the Technology Acceptance Model (TAM) as its theoretical basis, utilizing a purposive sampling method within a non-probability sampling framework and applying a quantitative research design. Data were collected through an online survey completed by 200 MSME respondents. For analysis, the study employed SEM-PLS technique, with SmartPLS version 4.0 for data processing. The findings reveal that perceived ease of use, trust, and financial literacy significantly and positively influence the intention to adopt sharia fintech. Conversely, perceived usefulness does not have a significant effect. It is also important to note that the study is limited by its sample size, which may restrict the generalizability of the finding to the broader MSME population in Indonesia.